2008
DOI: 10.2174/1874940200801010042
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Cooperativity in Inhibition of Protein Kinase a Catalytic Subunit

Abstract: Allosteric cooperativity in inhibition of protein kinase A was studied for the first time kinetically, by using the second-order rate constants of kemptide phosphorylation, measured in the absence and presence of inhibitors, and the effect of cooperativity was characterized in terms of the interaction factor . This kinetic method was evaluated for differently targeted inhibitors H89 and LRRAALG-NH 2 , and interaction of these compounds with the free enzyme and the enzyme-substrate complexes was quantified. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This trend had been previously observed, and the principle "better binding: stronger allostery" was formulated [10,11]. This qualitative pattern was formalized in terms of linear freeenergy relationships, as described below.…”
Section: Allosteric Interaction Between Atp and Peptidesmentioning
confidence: 57%
See 4 more Smart Citations
“…This trend had been previously observed, and the principle "better binding: stronger allostery" was formulated [10,11]. This qualitative pattern was formalized in terms of linear freeenergy relationships, as described below.…”
Section: Allosteric Interaction Between Atp and Peptidesmentioning
confidence: 57%
“…Our recent kinetic studies have revealed that the catalytic activity of protein kinase A was indeed governed by interaction between binding sites of two different substrates which can be said to be allosteric [10,11]. Moreover, allosterically regulated ligand binding properties have been observed for this enzyme also in several ligand binding studies, as summarized below.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations